PENGARUH PENERAPAN MODEL PEMBELAJARAN MEANS ENDS ANALYSIS MENGGUNAKAN MEDIA VIDEO TERHADAP KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 3 PAGAR ALAM - Yessy Novita Sari (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This research aimed to prove the influence of learning models means-ends analysis using video media against the active learning of the students on economic subject at SMA Negeri 3 Pagar Alam. This research was a experiment research, which used pre-experimentaldesign with pretest-posttest design. The population in this research was the entire class 10th students at SMA Negeri 3 Pagar Alam. The sample in this research used cluster random sampling and was selected to the class of 10th.2 as class experiments with 31 students. Data collection techniques were used in this research was a observational. The hypothesis used statistical regression formula with that simple parametris and correlation pearson product moment and retrieved Fhitung > Ftabel and thitung > ttabel then the hypothesis Ho is rejected and the Ha are received. Then it can be inferred that there is an influence of learning models means-ends analysis using video media against the active learning of the students on economic subject at SMA Negeri 3 Pagar Alam. Suggestions in this research, teachers should customized the class at the time of the activities of the ongoing discussions, the teachers should alsoalways guide the students to ask questions in the discussion. In addition, the learning model of applying means-ends analysis using video media subjects teachers should also guide the learners in making a conclusion at the goup presentation.